Mudhorobah At Micro Small Medium Enterprise “Small and Strong” - Wahyudi, Heru; Ansori, Muslich (International Journal of Economics, Business, and Entrepreneurship, 2018)
This research aims to find out the self regulating profit and loss sharing (PLS) facing the increase of regional minimum wage (RMW) at micro small and medium enterprise (MSME) in Indonesia. The background of this research the existence of wage conflict and the threat of urgency of MSME due to the policy of RMW. The theory used is the self regulating of Ediorno and theory profit and loss sharing of Ibn kaldun. The method used case study research conducted on MSME PtM in 6 districts in Lampung Province. Based on its explanation level, this study is a descriptive-comparative study. While based on its objectives, this research is applied research . Processed data are PLS of PtM and RMW in Lampung Province. This study is important to show the self regulating profit and loss sharing (PLS) at MSME as solution wage problem. The results showed that; MBM in MSME PtM has self regulating against UMR increase. The results of this study are in line with Ibn Taimyah "iwad al mithl", Ibn Khaldun "profit sharing as a fair way of dividing the production surplus", Zubair "gharor on the wage system because of prefixed like interest", Ediarno "wage system makes the economy not self regulating, high risk of crisis, perennial-wage conflict ", Setiawan" PLS system works better in generating profitability, more equitable in distributing wages, and creating higher productivity ", Keynes" wege rigidity causes self-regulating failure " , Pigou "elastic wage model (plasticity of wage) for the economy to be adaptive" self regulating ". The result of the study differs from Smith's thought that "classical economic flow" of the wage system in the production system would be "self-regulating," Ricardo's idea of the new clasisical economy "the classical market economy mechanism of surplus production rights of employers (employers)." Also different from Marx the right of surplus production belongs only to the workers.